1997
DOI: 10.1017/s1357729800015514
|View full text |Cite
|
Sign up to set email alerts
|

The effects of feeding high concentrations of molasses and supplementing with nitrogen and unprotected tallow on intake and performance of dairy cows

Abstract: A series of three replicated 3 × 3 Latin-square design experiments was carried out with lactating dairy cows (15 in experiments 1 and 3, and 18 in experiment 2). The objectives of these experiments were to investigate if the feeding of high concentrations of molasses would be detrimental to the performance or health of cows, and if the strategic supplementation of nitrogen or unprotected fat could enhance the efficiency of molasses feeding. In experiment 1, complete diets were based on grass silage with three … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
1
1
2

Year Published

1999
1999
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 15 publications
1
1
1
2
Order By: Relevance
“…The our results differ from the conclusions of Yan et al (1997) who reported that increase of the content of molasses in the lactating The cows fed soybean molasses supplemented ration had a higher milk protein concentration and yield relative to cows from control group (3.92 and 8.64 %, respectively), (P˂0.01). By including soybean molasses into ration the portion of readily degradable fractions of carbohydrates in rumen increases, which is likely to contribute to better energy supply of microorganisms and consequently higher rate of microbial protein synthesis from available non-protein nitrogen.…”
Section: Resultscontrasting
confidence: 99%
“…The our results differ from the conclusions of Yan et al (1997) who reported that increase of the content of molasses in the lactating The cows fed soybean molasses supplemented ration had a higher milk protein concentration and yield relative to cows from control group (3.92 and 8.64 %, respectively), (P˂0.01). By including soybean molasses into ration the portion of readily degradable fractions of carbohydrates in rumen increases, which is likely to contribute to better energy supply of microorganisms and consequently higher rate of microbial protein synthesis from available non-protein nitrogen.…”
Section: Resultscontrasting
confidence: 99%
“…Similar results were reported by Yan et al. ( 1997 ) that when the inclusion rate of molasses increased from 156 to 468 g/kg, DM improved milk protein concentration from 31.6 to 33.6 g/kg for mid‐lactation cows. Keady and Murphy ( 1998 ) observed that supplementing sucrose (10 g/kg DM) significantly increased milk protein concentration of lactating dairy cows.…”
Section: Discussionsupporting
confidence: 89%
“…Yan et al (1997) demonstrated that when molasses inclusion in the diets fed to mid-lactation cows increased from 156 to 468 g/kg DM, milk protein concentration increased from 31.6 to 33.6 g/kg. Keady and Murphy (1998) observed that supplementing sucrose (10 g/kg DM) significantly increased milk protein concentration of lactating dairy cows.…”
Section: Discussionmentioning
confidence: 99%